Exploring EFL speaking anxiety among junior high school students: Levels, contributing factors, and coping strategies - Prameswari, Novina Permata; Wahjuningsih, Eka; Imamyartha, David; Puspa, Areta (Journal of Research on English and Language Learning (J-REaLL), 2025)
While numerous studies have examined foreign language speaking anxiety at the university setting, research focusing on younger learners remains limited. This study addresses that gap by exploring the triggers and coping strategies to mitigate foreign language speaking anxiety among junior high school students. Exploring these two areas provides the avenue for wider opportunities of reaching higher proficiency levels at later stages, while allowing the identification of age- and gender-supportive coping strategies. Employing a mixed-method design, data were gleaned from questionnaires and semi-structured interviews involving six students—three male and three female—recruited after pondering their high rate of anxiety as measured by the Foreign Language Classroom Anxiety Scale (FLCAS). A content analysis revealed seven primary causes of anxiety: lack of vocabulary, performing in front of the class, fear of being laughed at, fear of making mistakes, fear of mispronouncing a word, fear of being the focus of attention, and fear of failure in English tests. Students adopted various coping strategies, including self-reassurance, calming techniques, and peer support. These findings highlight the need for teachers to recognize anxiety symptoms and implement fun and supportive strategies in the classroom. This study seeks to facilitate the students in overcoming and reducing the English-speaking anxiety they experienced during classroom practice. Due to the absence of in-depth investigation on the strategies to address anxiety, future researchers are advised to investigate the strategies that students engage in regulating their foreign language speaking anxiety and identify the coping mechanisms found most impactful in reducing anxiety levels.